POSITRON IMPACT IONIZATION OF ALKALI ATOMS - CAMPEANU, R. I. (Studia Universitatis Babeș-Bolyai Physica, 2020)
The models CPE and CPE4, which were successfully used in positron impact ionization studies, are applied to positron impact ionization of Li, Na and K. This work produces total cross sections which are in agreement with the existing theoretical papers and shows the necessity for experimental measurements of these processes.